Delhi diary - "Gandhi, M.K." (Ahmedabad, 1948)
This antiquairan volume contains a transcript of a diary kept by Mahatma Gandhi. The entries of the diary are dated between April 13th to December 29th, 1947, and were written during the year of Indian Independence. This book is highly recommended for anyone with an interest in the life and mind of this great leader, and it would make for a worthy addition to any personal collection. The chapters of this text include: ''Publishers Note'', ''Foreword By Rajendra Prasad'', ''City of the Dead'', ''The Refugee Problem'', ''A True Sikh'', ''News from N.W.F.P.'', ''Anger is Short'', ''Madness'', ''Forget the Past'', ''Rashtriya Swayamsevak Sangh'', ''Trust the Government'', ''God is the Refuge of All'', etcetera. Many vintage books such as this are increasingly scarce and expensive, and it is with this in mind that we are republishing this volume now, in an affordable, high-quality, modern edition. It comes complete with a specially commissioned biography of the author.
Keywords: "Gandhi, M.K."